Mortality in parents after the death of a child. (October 2019) - Song, Jieun; Mailick, Marsha R.; Greenberg, Jan S.; Floyd, Frank J.
Abstract: Objective: The death of a child is a traumatic stressor that takes a toll on the health of parents. This study examined long-term impacts of the death of a child on the risk of early mortality in bereaved parents. In a follow-up analysis, a twin subsample was analyzed to examine potential genetic confounding. Method: We analyzed data from the Midlife in the United States (MIDUS) study. The primary sample consists of two groups of MIDUS 2 participants (2004–06); (1) parents who experienced the death of a child prior to MIDUS 2 (n = 451) and (2) comparison parents who had not experienced death of any children (n = 1804) (mean age = 63). We also analyzed 52 twin pairs in which one twin experienced the death of a child and 271 twin pairs in which both twins had all living children. Mortality status of parents was assessed in 2017. Results: Parents who had experienced the death of a child had a 32% higher likelihood of early mortality (defined as dying earlier than life expectancy) than their peers who did not have any deceased children, and they were more likely to die of heart disease. Analyses of the twin subsample revealed significantly lower concordance for early mortality among the pairs with a bereaved twin than among control twins, consistent with non-genetic effects. Conclusions: The findings suggest that the death of a child has lasting impacts on the risk of early mortality in bereaved parents. This study provides the first U.S. estimate of bereavement effects on mortality extending through the parents' full life course, with significant public health implications. In addition, analysis of concordance of early death rates in the twin subsample suggests the impact on mortality of parental bereavement, net of genetic factors. Highlights: 32% higher rate of mortality in bereaved parents than non-bereaved parents. Parental mortality effect confirmed in twin sample. Highest death rates from heart disease in bereaved parents.